2021
DOI: 10.1093/ehjcr/ytab132
|View full text |Cite
|
Sign up to set email alerts
|

A ‘shark’-masked electrocardiogram: case report of a Tako-Tsubo syndrome

Abstract: Background Triangular ST-segment elevation or ‘shark-fin’ sign has been described as a specific indicator of acute coronary occlusion and large myocardial ischaemia, translating into poorer prognosis. However, this electrocardiographic presentation has been reported in rare cases of Tako-Tsubo syndrome and associated with more severe physical stressors and neurological involvement. Case summary We present a rare case of a 51-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…After treatment, recovery of cardiac function was reported in most studies 13,17,18,[22][23][24][25] . In 9 case reports, patients showed a satisfactory clinical response, with hemodynamic stabilization at discharge, followed only by gradually discontinued symptomatic treatment [16][17][18][19][20][21][22][23][24][25] . Only one study reported death as a result of acute heart failure 13 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…After treatment, recovery of cardiac function was reported in most studies 13,17,18,[22][23][24][25] . In 9 case reports, patients showed a satisfactory clinical response, with hemodynamic stabilization at discharge, followed only by gradually discontinued symptomatic treatment [16][17][18][19][20][21][22][23][24][25] . Only one study reported death as a result of acute heart failure 13 .…”
Section: Discussionmentioning
confidence: 91%
“…The angiography findings were normal in all patients. Significant recovery of LVEF was reported days and/or weeks after discharge from these patients in six studies 13,17,[22][23][24][25] .…”
Section: Takotsubo Cardiomyopathy and Epilepsymentioning
confidence: 98%
See 2 more Smart Citations
“…Verdoia et al reported a case of a 51 years old female that developed TTC post-sepsis in the ICU with the SFE sign. The patient regained complete sinus rhythm post-acute management and was subsequently followed up for a period of six months [18].…”
Section: Discussionmentioning
confidence: 99%